2013
DOI: 10.1021/cn4000583
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation at the Delta Opioid Receptor of a Series of Linear Leu-Enkephalin Analogues Obtained by Systematic Replacement of the Amides

Abstract: Leu-enkephalin analogues, in which the amide bonds were sequentially and systematically replaced either by ester or N-methyl amide bonds, were prepared using classical organic chemistry as well as solid phase peptide synthesis (SPPS). The peptidomimetics were characterized using competition binding, ERK1/2 phosphorylation, receptor internalization, and contractility assays to evaluate their pharmacological profile over the delta opioid receptor (DOPr). The lipophilicity (LogD7.4) and plasma stability of the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 75 publications
1
54
0
Order By: Relevance
“…Among all compounds tested, analog 17 showed the highest affinity (K i = 89 nM) for DOPr (Table 1). At this fourth amide position, we previously showed that introducing an E-alkene induced an even larger decrease in the affinity, 11 while the replacement by the hydrogen bond acceptors ester 12 and N-Methyl amide 12 generated peptidomimetics almost as potent as Leu-enkephalin itself (K i = 6.3 nM). 11 The analog 17 also displayed a weak potency to inhibit electrical field-induced mouse vas deferens contraction (Table 1) and to induce ERK1/2 phosphorylation ( Figure S1).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Among all compounds tested, analog 17 showed the highest affinity (K i = 89 nM) for DOPr (Table 1). At this fourth amide position, we previously showed that introducing an E-alkene induced an even larger decrease in the affinity, 11 while the replacement by the hydrogen bond acceptors ester 12 and N-Methyl amide 12 generated peptidomimetics almost as potent as Leu-enkephalin itself (K i = 6.3 nM). 11 The analog 17 also displayed a weak potency to inhibit electrical field-induced mouse vas deferens contraction (Table 1) and to induce ERK1/2 phosphorylation ( Figure S1).…”
mentioning
confidence: 91%
“…In previous studies, we have shown that the systematic replacement of amides in Leuenkephalin by E-alkenes 11 , esters 12 and N-Methyl amides 12 can reveal important information regarding the biological role of each amide in relevant analogs of Leuenkephalin and can therefore increase our understanding of the non-covalent interactions between DOPr and its endogenous ligands. To our knowledge the use of a triazole as a dipeptide isostere has never been applied to the field of opioid peptidomimetics, although some tetrazoles mimicking cis-amides have already been reported 5d .…”
mentioning
confidence: 99%
“…There are some reports that DPDPE and deltorphins can cross the blood-brain barrier (Williams et al, 1996; Fiori et al, 1997); and there has also been some effort to make more stable peptidomimetics (Rochon et al, 2013). In addition, considerable effort has been expended in developing small molecule (non-peptide) agonists to study the delta opioid receptor.…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical administration of Leu‐enkephalin is limited by a poor pharmacokinetic (PK) profile, including rapid proteolysis of Tyr 1 ‐Gly 2 by aminopeptidase N in human plasma ( t 1/2 =0.69 min; 0.50 U mL −1 purified enzyme) and of Gly 3 ‐Phe 4 by angiotensin‐converting enzyme at the blood–brain barrier ( t 1/2 =130 min; 0.12 U mL −1 purified enzyme), both of which inhibit penetration into the central nervous system . To improve potency and selectivity, many cyclic and linear analogues of enkephalin have been developed that possess excellent affinities and selectivities for the DOPR, and in some cases, the replacement of hydrolyzable amide bonds at various positions with peptidomimetics (e.g., trans ‐alkene, thioamide, ester or N ‐methyl amide dipeptide isostere) have modulated stability and PK properties of enkephalins, without major loss of agonist activity at the DOPR. However, many of these analogues still lack appropriate physicochemical and biophysical properties for in vivo use.…”
Section: Figurementioning
confidence: 99%